Field Assessment of Gravel Loss on Unsealed Roads in Australia - Pardeshi, Vasantsingh; Nimbalkar, Sanjay; Khabbaz, Hadi (Frontiers in Built Environment, 2020)
The gravel loss is a major limitation for unsealed roads and attracts major maintenance annually. The continual process of gravel loss also makes roads environmentally unsustainable. The unsealed road management faces several issues viz. difficulty to forecast behavior, huge data collection needs, a vulnerability in the service and maintenance practices. The quality of gravel material also plays a major role in the process of gravel loss. In view of this, appropriate revisions to ARRB material specifications are proposed in this paper. The gravel material as per modified ARRB specifications is used on the unsealed road network in the Scenic Rim Regional Council in the state of Qld. Gravel loss monitoring stations are established over the entire region in order to assess the gravel loss and the implication of using better quality gravel. This paper discusses the gravel loss monitoring approaches, data analyses and improved material specification for gravel. It is found that the modified gravel used on unsealed road performs better than conventionally used gravel.